Contribution of Citizen Journalism as a Tool for Development Communication in Sri Lanka - Siriwardhana, Krishan Jayashanka (My University, 2012)
The Media and Communication industry has undergone significant changes in the last few decades due to rapid developments in communication technology. The media landscape has been divided in to two main categories as traditional media and new media in the current context. New Media is the interactive forms of communication that use internet, blogs, social media, text messages and virtual worlds. Citizen Journalism is one of the most significant characteristics of New Media which brought a paradigm shift by empowering the ordinary citizen to be an active contributor in the journalism process. Shayne Bowman and Chris Willis (2010) describe citizen journalism as the act of a citizen, or group of citizens, playing an active role in the process of collecting, reporting, analyzing and disseminating news and information. Citizen Journalism promotes and gives prominence to the information and news which are left out by the mainstream media due to political and ideological agendas. The role of Citizen Journalism is to build more interconnected communities through citizens empowering each other with accurate news and information. Citizen Journalism provides an independent voice and a space for expression to people on political, economic and social issues of their society. Media consumers had a very limited opportunity to convey feedback, share their views and comments in traditional media due to the inherited characteristics of newspaper, television and Radio. Websites, blogs and social media have not only given the opportunity to its users to comment and share their thoughts, but also users are given the opportunity to generate their content as journalists. New Media tools have become familiar to Sri Lankan users and there is an increasing use of Citizen Journalism platforms in the country. This paper discusses the contribution of Citizen Journalism as a tool for development communication in Sri Lanka. In the contemporary context media is considered as the fourth state which is not merely an information provider, but a crucial phenomenon which can be used for the development of the human being. Development Communication is identified as one of the main functions of media in the current context. As post war Sri Lanka is looking forward to development in social, economic and cultural aspects, the study focuses on how Citizen Journalism has contributed in addressing development issues. As blogging is a leading Citizen Journalism platform in the current media age, five leading blog sites are selected for analysis. Selection of blogs is based on the internet ranking. A content analysis of selected blog sites is conducted in this study. The representation of development issues in the selected blog sites will be analyzed in the research. A questionnaire is distributed among the readers of the selected blog sites to identify the impact of the development issues reported in the blogs.